2014
DOI: 10.1103/physrevb.90.134311
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced densification under shock compression in porous silicon

Abstract: Under shock compression, most porous materials exhibit lower densities for a given pressure than that of a full-dense sample of the same material. However, some porous materials exhibit an anomalous, or enhanced, densification under shock compression. We demonstrate a molecular mechanism that drives this behavior. We also present evidence from atomistic simulation that pure silicon belongs to this anomalous class of materials. Atomistic simulations indicate that local shear strain in the neighborhood of collap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 33 publications
(34 reference statements)
0
17
0
1
Order By: Relevance
“…Our simulations are carried out with the MOD interatomic potential [33], which predicts a melting T of 1680 K at P=0 GPa. Simulations by Lane and coworkers [36]…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%
“…Our simulations are carried out with the MOD interatomic potential [33], which predicts a melting T of 1680 K at P=0 GPa. Simulations by Lane and coworkers [36]…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%
“…Recent molecular dynamics (MD) simulations for germanium [36] and silicon [2,23,37] shocked along [100] cd have suggested that the transformation mechanisms for structural changes between the cd silicon and the β-Sn, Imma and sh structures are more complex than commonly assumed [12,14,15,18,[30][31][32][33][34][35]. An interesting finding of the MD simulations was that the transformations occurred along shear bands [2,36,37] which were attributed to planar stacking faults [36,37].…”
Section: The Dynamic Compression Sector (Dcs) At the Advanced Photon mentioning
confidence: 99%
“…An interesting finding of the MD simulations was that the transformations occurred along shear bands [2,36,37] which were attributed to planar stacking faults [36,37]. However, the MD simulations [2,36,37] predicted a peak state which was in a mixed phase rather than the completely transformed material. Additionally, the high pressure structure determined from MD simulations for shocked Si(100) was identified as Imma [2] or amorphous [23].…”
Section: The Dynamic Compression Sector (Dcs) At the Advanced Photon mentioning
confidence: 99%
“…Regarding silicon, there are several shock experiments at applicable strain rates 2 12 13 14 in addition to multiple MD simulations 2 13 14 15 16 . Notably, Smith et al 17 used laser-driven shocks to measure the elastic limit as a function of strain rate.…”
mentioning
confidence: 99%